The relationship between parenting and the manifestation of perfectionism among Greek college students - Czepiel, Diana; Τάνταρος, Σπυρίδων (Psychology: the Journal of the Hellenic Psychological Society, 2018)
Previous research suggests that the origins of perfectionism lie in parental factors. The present study examined how parenting style and family perfectionism is associated with the manifestation of perfectionism in a sample of 855 Greek university students, using the Almost Perfect Scale-Revised (APS-R), the Family Almost Perfect Scale (FAPS) and the Parental Authority Questionnaire (PAQ). The subscales of APS-R and FAPS are combined to provide three types of personal and family perfectionism respectively (adaptive, maladaptive, absence of perfectionism), whereas PAQ distinguishes three parenting styles (authoritarian, permissive, authoritative). The authoritative parenting style was positively associated with adaptive perfectionism in both genders and negatively associated with maladaptive perfectionism among women, the authoritarian parenting style was positively associated with maladaptive perfectionism among men, whereas the permissive parenting style was positively associated with maladaptive perfectionism among women and the absence of perfectionism among men. Moreover, the type of personal perfectionism was associated to the respective type of family perfectionism.